2018
DOI: 10.3892/or.2018.6619
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanisms of celastrol on the apoptosis of HOS osteosarcoma cells

Abstract: Osteosarcoma is the most common primary malignant tumor of the bone found predominantly in children and teenagers and results in early metastasis and poor prognosis. The present study primarily focused on the impact of celastrol on apoptosis and autophagy of osteosarcoma HOS cells, as well as the related mechanisms. Following the appropriate treatment, the human osteosarcoma cell line HOS was assessed for viability, Ca2+ in cells, apoptosis and changes in cell morphology using Cell Counting Kit-8, flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Hepatocyte apoptosis is characterized by nuclear chromatin condensation, nuclear rupture, cell contraction, plasma membrane vacuolation, DNA damage, lack of nutrition and cytokine release, which reflect the activation of cell surface death receptors and apoptotic factors. 8790…”
Section: The Outcomes Of Liver Cell Caused By Mnpsmentioning
confidence: 99%
“…Hepatocyte apoptosis is characterized by nuclear chromatin condensation, nuclear rupture, cell contraction, plasma membrane vacuolation, DNA damage, lack of nutrition and cytokine release, which reflect the activation of cell surface death receptors and apoptotic factors. 8790…”
Section: The Outcomes Of Liver Cell Caused By Mnpsmentioning
confidence: 99%
“…While Zheng et al did not explore whether IL-17 was elevated in their obese mice experiencing airway allergic responses, they do find neutrophil infiltration increased in the lung, and Th17 cells play an important role in recruiting neutrophils [75,186]. Treating obese mice with celastrol, a drug known to promote apoptosis in cancer cells via activation of IRE1, ATF4, and CHOP, reduces airway hyperresponsiveness and IL-17 production [185,187,188,189]. These studies indicate that targeting UPR in obesity mediated asthma may prove beneficial for treatment.…”
Section: Upr T Cells and Diseasementioning
confidence: 99%
“…Extensive experimentation has indicated that autophagy modulation may be an important mechanism underlying the anti-tumor therapeutic effect of celastrol (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Celastrol also alleviates inflammatory reactions and restrains the immune response through autophagic pathways (31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Autophagy Regulation By Celastrolmentioning
confidence: 99%